California poppy (Eschscholzia californica), the Papaveraceae golden girl model organism for evodevo and specialized metabolism - Becker, Annette; Yamada, Yasuyuki; Sato, Fumihiko (Frontiers in Plant Science, 2023)
California poppy or golden poppy (Eschscholzia californica) is the iconic state flower of California, with native ranges from Northern California to Southwestern Mexico. It grows well as an ornamental plant in Mediterranean climates, but it might be invasive in many parts of the world. The California poppy was also highly prized by Native Americans for its medicinal value, mainly due to its various specialized metabolites, especially benzylisoquinoline alkaloids (BIAs). As a member of the Ranunculales, the sister lineage of core eudicots it occupies an interesting phylogenetic position. The California poppy has a short-lived life cycle but can be maintained as a perennial. It has a comparatively simple floral and vegetative morphology. Several genetic resources, including options for genetic manipulation and a draft genome sequence have been established already with many more to come. Efficient cell and tissue culture protocols are established to study secondary metabolite biosynthesis and its regulation. Here, we review the use of the California poppy as a model organism for plant genetics, with particular emphasis on the evolution of development and BIA biosynthesis. In the future, California poppy may serve as a model organism to combine two formerly separated lines of research: the regulation of morphogenesis and the regulation of secondary metabolism. This can provide insights into how these two integral aspects of plant biology interact with each other.